Agroecology and sustainable food systems: Participatory research to improve food security among HIV-affected households in northern Malawi. (September 2016) - Nyantakyi-Frimpong, Hanson; Mambulu, Faith Nankasa; Bezner Kerr, Rachel; Luginaah, Isaac; Lupafya, Esther
Abstract: This article shares results from a long-term participatory agroecological research project in northern Malawi. Drawing upon a political ecology of health conceptual framework, the paper explores whether and how participatory agroecological farming can improve food security and nutrition among HIV-affected households. In-depth interviews were conducted with 27 farmers in HIV-affected households in the area near Ekwendeni Trading Centre in northern Malawi. The results show that participatory agroecological farming has a strong potential to meet the food, dietary, labour and income needs of HIV-affected households, whilst helping them to manage natural resources sustainably. As well, the findings reveal that place-based politics, especially gendered power imbalances, are imperative for understanding the human impacts of the HIV/AIDS epidemic. Overall, the study adds valuable insights into the literature on the human-environment dimensions of health. It demonstrates that the onset of disease can radically transform the social relations governing access to and control over resources (e.g., land, labour, and capital), and that these altered social relations in turn affect sustainable disease management. The conclusion highlights how the promotion of sustainable agroecology could help to partly address the socio-ecological challenges associated with HIV/AIDS. Highlights: We describe a long-term agroecological farming practices among HIV/AIDS farmers in Malawi. HIV-affected farmers are using agroecology to improve food security. HIV-affected farmers report improved changes in dietary diversity as a result of agroecological farming. Study results show why gender politics should be central in political ecology of health research.